2007
DOI: 10.1002/ibd.20262
|View full text |Cite
|
Sign up to set email alerts
|

Early bacterial dependent induction of inducible nitric oxide synthase (iNOS) in epithelial cells upon transfer of CD45RBhigh CD4+ T cells in a model for experimental colitis

Abstract: These findings demonstrate that the expression of epithelial iNOS is highly bacterium-specific and correlates with the severity of disease, suggesting an important role for this enzyme in the development of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The NFκB mediated inducible nitric oxide synthase was equally increased in the inflamed ileum of both ATG16L1 genotypes36 (see online supplementary figure S3A). Except for 1 patient homozygous for the ATG16L1 protective allele, the defensin 5 and 6 gene expression (Paneth cell function) decreased upon inflammation in all other patients (p<0.05 for risk allele group) (figure 4A,B).…”
Section: Resultsmentioning
confidence: 93%
“…The NFκB mediated inducible nitric oxide synthase was equally increased in the inflamed ileum of both ATG16L1 genotypes36 (see online supplementary figure S3A). Except for 1 patient homozygous for the ATG16L1 protective allele, the defensin 5 and 6 gene expression (Paneth cell function) decreased upon inflammation in all other patients (p<0.05 for risk allele group) (figure 4A,B).…”
Section: Resultsmentioning
confidence: 93%
“…Recently, Kretzmann et al [43] showed that inhibition of iNOS may contribute to the therapeutic effect of glutamine in rats with 2,4,6-trinitrobenzene sulfonic acid-induced colitis. Dijkstra et al [44] also reported that the expression of epithelial iNOS is highly bacterium-specific and can correlate with the severity of the disease, suggesting an important role for this enzyme in the development of IBD. Therefore, the anti-colitis activity of W. chinesis may be mediated in part via its effect on inhibition of iNOS activation in colon tissues.…”
Section: Discussionmentioning
confidence: 98%
“…Changes in the microbial content of the gut also lead to an imbalance between the beneficial metabolic byproducts and bacterial toxic compounds [14]. Furthermore, both culture-dependent methods and molecular approaches have shown that dysbiosis of the gut bacterial community leads to overexpression of antigenic bacterial surface proteins, which results in an exaggerated immune response and chronic immune-mediated inflammatory mucosal damage in IBD patients [1517]. In stools from patients with colorectal carcinoma, an increase in the proportion of bacteria such as Bacteroides spp.…”
Section: Introductionmentioning
confidence: 99%